Delivery of proteins into living cells by reversible membrane permeabilization with streptolysin-O - Walev, Iwan (The National Academy of Sciences, 2001)
The pore-forming toxin streptolysin O (SLO) can be used to reversibly permeabilize adherent and nonadherent cells, allowing delivery of molecules with up to 100 kDa mass to the cytosol. Using FITC-labeled albumin, 10(5)–10(6) molecules were estimated to be entrapped per cell. Repair of toxin lesions depended on Ca(2+)-calmodulin and on intact microtubules, but was not sensitive to actin disruption or to inhibition of protein synthesis. Resealed cells were viable for days and retained the capacity to endocytose and to proliferate. The active domains of large clostridial toxins were introduced into three different cell lines. The domains were derived from Clostridium difficile B-toxin and Clostridium sordelli lethal toxin, which glycosylate small G-proteins, and from Clostridium botulinum C2 toxin, which ADP-ribosylates actin. After delivery with SLO, all three toxins disrupted the actin cytoskeleton to cause rounding up of the cells. Glucosylation assays demonstrated that G-proteins Rho and Ras were retained in the permeabilized cells and were modified by the respective toxins. Inactivation of these G-proteins resulted in reduced stimulus-dependent granule secretion, whereas ADP-ribosylation of actin by the C. botulinum C2-toxin resulted in enhanced secretion in cells. The presented method for introducing proteins into living cells should find multifaceted application in cell biology.